Omicron (B.1.1.529) BA.1 or BA.2-related effects on immune responses in previously naïve versus imprinted individuals: immune imprinting as an advantage in the humoral immune response against novel variants - Sonnleitner, Sissy Therese; Walder, Samira; Knabl, Ludwig; Poernbacher, Roswitha; Tschurtschenthaler, Thomas; Hinterbichler, Eva; Sonnleitner, Stefanie; Muehlmann, Viktoria; Posch, Wilfried; Walder, Gernot (Frontiers in Immunology, 2023)
SARS-CoV-2 strain B.1.1.529 (Omicron) has split into different strains in the course of 2022 and developed numerous mutations, mainly in the region coding for the spike protein. This region is the main target for serologic immune response following natural infection and vaccination as well. In this study we investigated (i) how immune imprinting by previous infection or vaccination affects the immune response to a subsequent infection with Omicron BA.1 or BA.2, (ii) if there are differences in the antibodies formed in naïve patients and imprinted patients (iii) the neutralization capacity against the currently predominant strain BA.5 in both groups and (iv) gives evidence that more severe courses of infection are linked to a reduced or non-concerted T and B cell response. This was done by antibody measurement, immunoblot analyses, IFN-γ ELISpot and plaque-reduction neutralization test. Our findings show significant differences in the humoral and cellular immune response of naïve versus imprinted patients. Imprinted participants developed significantly higher antibody titers and showed significantly stronger neutralization capacity against the wildtype, BA.1 and BA.5 as a result of previous infection with BA.1 or BA.2. The immune response of naïve study participants was narrower and related mainly to the receptor-binding domain, which resulted in a lower neutralization capacity against other strains including BA.5. Naïve study participants showed a significantly higher cellular immune response than the imprinted study group, indicating a higher antigenic challenge. The cellular immune response was directed against general structures of SARS-COV-2 and not specifically against the receptor-binding domain.